Isolation and characterization of Salmonella phages and phage cocktail mediated biocontrol of Salmonella enterica serovar Typhimurium in chicken meat. (1st February 2022) - Anjay,; Kumar, Ashok; Abhishek,; Malik, Hina; Dubal, Zunjar Baburao; Jaiswal, Rohit Kumar; Kumar, Suman; Kumar, Bablu; Agarwal, Rajesh Kumar
Abstract: The consumption of foods contaminated with Salmonella continues to be a serious public health concern that can be controlled by implementation of effective measures like application of lytic bacteriophages. In this study, 21 Salmonella bacteriophages were isolated from sewage samples. On transmission electron microscopy, 15 phages were identified as Myoviridae, 05 phages as Siphoviridae, and 01 phage as Podoviridae. Based on lytic spectrum, 15 phages have very wide while 06 phages wide host range. Before testing in the meat sample, all phages were further screened for sensitivity against S . Typhimurium, the strain frequently prevalent in meat and found sensitive against 22.03–81.36% strain. For testing the efficacy of phages as a biocontrol agent, phage cocktail was applied over raw chicken meat spiked with S . Typhimurium at 25 °C and 4 °C. At MOI of 100, 1000, and 10000 a significant reduction of 1.17, 1.26, and 1.31 log10 CFU/g in the viable count of S . Typhimurium was observed at 7 h post phage application, in comparison to phage-free controls. However, at 4 °C a significant reduction of 1.29, 1.91, 2.48 log10 CFU/g was achieved after 7 days of incubation. This work intimidates the use of phages for biocontrol of S. Typhimurium in chicken meat. Highlights: 21 lytic Salmonella phages were isolated from sewage samples. 15 phages of Myoviridae, 05 Siphoviridae and 01 Podoviridae were identified by TEM. Phages were found to lyse the S. Typhimurium (ST) strains from diverse sources. Phage cocktail treatment exhibited a significant reduction of ST in chicken meat. These lytic phages have a high potential for their use as biocontrol agent.